CUSTOMER INTENTION SEBAGAI MEDIASI PERCEIVED USEFULNESS DAN PERCEIVED PRICE TERHADAP BUYING DECISION KONSUMEN YOUTUBE PREMIUM DI BALI - Desak Made Febri Purnama Sari; Ignacia Linda Marcelina (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to measure the effect of perceived usefulness and perceived price on buying decisions through customer intention on YouTube Premium services. The number of samples in this study was 119 YouTube Premium users in Bali, who were taken using a purposive sampling technique. Data were analyzed using Partial Least Square, one of the Structural Equation Modeling approaches. The results showed that perceived usefulness had a positive and significant effect on customer intention, perceived price had a positive and significant effect on customer intention, and customer intention had a positive and significant effect on buying decisions. Another finding was that customer intention mediated the effect of perceived usefulness and perceived price on buying decisions. The results of this study can be used as a reference for improving the quality of YouTube Premium services by increasing the benefits of using and offering prices through discounted, voucher, or gift card schemes. Keywords: buying decision, customer intention, perceived price, perceived usefulness